Diversity and abundance of butterflies in Tokha Municipality, Kathmandu, Nepal - Chataut, Prakriti; Rokka, Smriti (Nepalese Journal of Zoology, 2025)
This study investigated the diversity and abundance of butterflies in Tokha Municipality, Ward No. 2 and 3, Kathmandu, Nepal from November 2023 to January 2024 using pollard walk method. During the study period, 219 individuals of 47 butterfly species were documented, with an overall Shannon-Wiener diversity index (H) of 3.17 and an evenness (E) of 0.823. The study area encompasses 3 different habitats: forest, agriculture land and settlement area where the forest habitat had the highest species richness (H= 29). Among the 6 families detected, Nymphalidae family was the most dominant with 19 species. When assessing the diversity on a monthly basis, the species richness was the highest in November (N=32) and least in January (N=16). This study provides baseline data for monitoring the butterfly population under the influence of rapid urbanization and environmental changes occurring in this area.